Need for Animal Models of Meibomian Gland Dysfunction. Issue 2 (December 2016) - Tong, Louis; Gupta, Preeya.
Abstract Evaporative dry eye has gained increasing interest in recent years in academia, pharmaceutical, and medical device industries. The main cause of this type of dry eye is attributed to meibomian gland dysfunction (MGD). MGD is a diffuse abnormality of the meibomian glands characterised by terminal duct obstruction and eventually leading to signs and symptoms of dry eye. There have been only a few reported animal models of MGD, but recent advances are likely to lead to new models and better ways to assess the pathology in these animals. Recent models reported include one based on cautery of the meibomian glands in mice and another based on aggravated allergy in mice. These developments will enable better pre-clinical assessment of novel therapies in the future.